Financial Performance and PROPER Ratings Impact on Corporate Environmental Responsibility Disclosure - Baroroh, Niswah; Anisykurlillah, Indah; Rizkiana, F. R.W.; Setiyaningrum, R. (Economic Education Analysis Journal, 2023)
The corporate disclosure of environmental responsibility for companies is crucial in building transparency, trust and maintaining sustainability, showing their commitment to environmental sustainability. Corporate sustainability is closely related to the company's financial performance and external assessment. This research purposed to analyze the profitability, size and leverage as the corporate financial performance and PROPER rating as the external assessment on environmental evaluation. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021. This study uses panel data regression analysis with a regression model in the form of Random Effect Model and Moderating Regression Analysis using E views 12. The results of this study indicate that the average of environmental disclosure in Indonesian companies is still relatively low, and the environmental performance is in moderate condition. Profitability, leverage and company size can’t influence the environmental disclosure. And then, the environmental performance variable as a moderating variable cannot strengthen or weaken the effect of profitability, leverage and company size on corporate social responsibility disclosure. Future research is expected to look for other variables that are more closely related to corporate social responsibility disclosure.